2018
DOI: 10.7717/peerj.5477
|View full text |Cite
|
Sign up to set email alerts
|

Trends in hepatocellular carcinoma research from 2008 to 2017: a bibliometric analysis

Abstract: ObjectivesTo comprehensively analyse the global scientific outputs of hepatocellular carcinoma (HCC) research.MethodsData of publications were downloaded from the Web of Science Core Collection. We used CiteSpace IV and Excel 2016 to analyse literature information, including journals, countries/regions, institutes, authors, citation reports and research frontiers.ResultsUntil March 31, 2018, a total of 24,331 papers in HCC research were identified as published between 2008 and 2017. Oncotarget published the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 43 publications
1
62
0
2
Order By: Relevance
“…The IF of the journals publishing AS research ranged from 1.984 (Evidence-Based Complementary and Alternative Medicine) to 6.044 (Carbohydrate Polymers). As is shown in Figure 2, the dual-map overlay of journals represents the subject distribution of journals, with the left side of the graph representing citing journals, the right side of the graph indicating cited journals, and the colored lines representing the citation relationship between articles in citing journals and articles in cited journals (Chen, 2017;Miao et al, 2018). We found that there were three citation paths, including two orange paths and one yellow path.…”
Section: Journals Analysismentioning
confidence: 87%
See 3 more Smart Citations
“…The IF of the journals publishing AS research ranged from 1.984 (Evidence-Based Complementary and Alternative Medicine) to 6.044 (Carbohydrate Polymers). As is shown in Figure 2, the dual-map overlay of journals represents the subject distribution of journals, with the left side of the graph representing citing journals, the right side of the graph indicating cited journals, and the colored lines representing the citation relationship between articles in citing journals and articles in cited journals (Chen, 2017;Miao et al, 2018). We found that there were three citation paths, including two orange paths and one yellow path.…”
Section: Journals Analysismentioning
confidence: 87%
“…The top 10 references with the strongest strength citation burst identified by CiteSpace are presented in Figure 5. Papers with a high citation burst are paid much attention by peers in the scientific community, therefore emerging trends or topics within the AS research field were labeled in this study by AS publications with high citation bursts (Chen, 2017;Miao et al, 2018). Overall, the burst strength of the top 10 AS publications ranged from 2.5479 to 3.9294, while endurance strength ranged from 4 to 6 years, as indicated by the number of red squares.…”
Section: Emerging Topicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parallel with the globalization of science, spatial scientometric studies have become more common. As demonstrated by Frenken et al (2009a), spatial scientometrics initially involved the country level in the research focusthe works performed by Narin and Carpenter (1975) and Frame et al (1977) are considered particularly important in the fieldand the majority of spatial scientometric studies have still been focusing on examining the country level (see, for example, Almeida et al 2009;Gazni et al 2012;Glänzel 2001;Horta and Veloso 2007;Lee et al 2011;Leydesdorff et al 2014;Miao et al 2018;OECD and CSIC 2016;Stephan and Levin 2001;Wang et al 2017). Besides country-level scientometric analyses, based on experiences gained from them, many spatial scientometric studies have been carried out with sublevel territorial units (e.g., federal states, provinces, and NUTS regions 1 ) in focus.…”
Section: Introductionmentioning
confidence: 99%